Standards for Dimensions of Space and Environment in Buildings for People with Special Needs (i.e. Wheelchairs, Crutches, Canes for The Visually Impaired) - Ali Rahmat (Universitas Pendidikan Indonesia (UPI), 2021)
The purpose of this study is to describe the concept of basic dimensions of space and environment for persons with disabilities. This research was made by conducting a literature review. The results of the study were taken by taking data from the literature. The data is then processed to be presented in the form of an explanation that can be easily understood. Therefore, it is hoped that the research results can be used as a reference for the construction of buildings and the environment, especially for buildings in hospitals, schools, and public facilities for people with special needs (i.e. wheelchairs, crutches, and canes for the blind).